Takayasu 's Disease - A. Samik Wahab; Sunarto Sunarto; Aris Soebardi; Ryna Harlistyanti (Paediatrica Indonesiana, 1990)
A fourteen years old girl developed Takayasu 's arteritis (pulseless disease) since six months prior to investigation. This unusual form of arteritis is common in Japan and Korea but has rarely been reported in individuals born in the United States. In Indonesian literatu;e it has never been documented so far. The etiology is unclear. The literature currently but forward the hypothesis of an autoimmune basis and treatment with steroid. Although a tuberculin sensitization pathogenesis has been suggested, a close temporal relationship with the onset of a tuberculous process has not previously been documented. The likelihood of uncovering tuberculin sensitivity or active tuberculosis in patients with Takayasu, arteritis is substantially higher than in the general population in all countries analyzed. The natural history of his arteritis is highly variable. The adolescent described in this paper has demonstrated no response either to antituberculosis therapy, or to heparin and corticosteroid as suggested by Ishikawa, 1987. The patient died on the 59th day of hospitalization after getting syncopal attacks followed by shock.